Isolasi dan Karakterisasi Molekuler Gen 16S rRNA Bakteri Lipolitik Asal Limbah Kulit Biji Jambu Mete: Isolation and Molecular Characterization of Lipolytic Bacterial 16S rRNA Gene from Cashew Nutshell Waste - Muhamad Azwar Syah (Jurnal Sumberdaya Hayati, 2022)
Lipolytic bacteria attract great attention to various biotechnology industries because of their enzymatic potential. This study aims to isolate and identify lipolytic bacteria from cashew nutshell waste using the 16S rRNA gene as a molecular marker. Lipolytic bacteria were isolated using serial dilutions and inoculated on lipolytic media. A total of 3 isolates of lipolytic bacteria were obtained from cashew nutshell waste based on screening in LA Rhodamine B. The partial sequence of 16S rRNA gene from LB15 amplified using a pair of primers 63F and 1387R having a size of 1238 bp, while BL6 and BK6 were 1283 bp, respectively. Based on genetic distance analysis and phylogenetic reconstruction, we proposed that LB15 be identified as Burkholderia sp. with 99.92% similarity. In addition, because the 16S rRNA gene sequence similarity of BL6 was 99.87% with Paraburkholderia kururiensis strain 979, BL6 was classified as Paraburkholderia kururiensis. Then, isolate BK6 was identified as Ralstonia sp. with a similarity of 99.53%. The similarity value can be used as a reference in determining the identity of bacteria. A bacterium can be categorized as the same species if it has a similarity value of more than 99%.